Sosialisasi Sistem Aplikasi Pencatatan Informasi Keuangan (SIAPIK) pada UMKM Desa Karangrejo Petanahan - Pamuji Rahayu, Sri Rejeki; Mispiyanti (PT. Karya Inovatif Nusantara, 2024)
In general, the level of understanding of MSME players regarding accounting or financial recording transactions in Indonesia is still low. For this reason, activities are needed to provide financial literacy, one of which is the socialization of SIAPIK. The SIAPIK application can be used by MSMEs to carry out bookkeeping. The financial reports produced from the SIAPIK application are the financial position report or balance sheet, profit and loss report, retained earnings report, and cash flow report. All financial reports generated from the SIAPIK application are standardized. The method of implementing activities uses the experiential learning method. The aim of this community service activity is to equip MSMEs in preparing financial reporting standards for MSMEs, assisting MSMEs in preparing financial reports and assisting creditors in analyzing the capabilities of MSMEs when applying for credit or financing